State Responsibility for Victims of Domestic Violence - Sumarno Sumarno; Syahranuddin Syahranuddin (RIRAI Publisher, 2023)
The occurrence of violence in the household is still common due to a wrong understanding of gender bias, where a woman must submit to a man. In general, gender bias also places women in a weak position, thus making men more dominant in the family system and society, this is very detrimental to women, so women experience violence more often. Domestic violence is often called a hidden crime, because it is committed within the scope of the household which cannot be known by other people openly, and for victims it is also a separate dilemma considering that the perpetrators of violence are also family members (husband against wife or vice versa) who in fact are still in a marriage bond. the variables causing the wrongdoing of household savagery incorporate envy, financial variables, and a need of information almost existing enactment. Legitimate security for ladies casualties of household viciousness has been controlled in Law Number 23 of 2004 concerning the Disposal of Household Viciousness.